The Earnings Quality as a Partial Transmission Channel Between Corporate Governance and Firm Value: Evidence from Indonesian Manufacturing Firms - Robin; Etty Sri Wahyuni (Academic Bright Collaboration, 2026)
Purpose – This study examines whether earnings quality serves as a transmission mechanism linking Good Corporate Governance (GCG) to firm value, addressing inconsistent findings in prior literature. The key argument is that GCG does not directly enhance firm value but operates indirectly by first improving reported earnings quality, which the market subsequently rewards.Methods – This study analyzes 435 observations from 87 manufacturing companies listed on the Indonesia Stock Exchange (2019–2023). The primary analysis employs panel data regression with firm fixed effects and year dummies using Stata 17, complemented by pooled OLS path analysis in SPSS 27 as a robustness check. GCG is proxied by independent commissioners, audit committee size, institutional ownership, and managerial ownership. Earnings quality is measured using the McNichols model, and firm value by Tobin's Q. Mediation is tested through the Sobel Test and Bootstrapping (5,000 resamples) via PROCESS Macro Hayes.Findings – Independent commissioners (β = 0.194; p < 0.01) and institutional ownership (β = 0.237; p < 0.01) are positively associated with earnings quality, while managerial ownership is negatively associated (β = −0.142; p < 0.05). Audit committee size shows no significant association (p = 0.082). Earnings quality is positively associated with firm value (β = 0.318; p < 0.01). Bootstrapped indirect effects indicate that earnings quality partially mediates three of four GCG–firm value paths.Research implications – The sample is confined to manufacturing companies, limiting cross-sector generalizability. GCG measurement covers four mechanisms, excluding dimensions such as board meeting frequency and audit committee expertise. The observational design precludes definitive causal claims; associations are interpreted within the theoretical framework.Originality – This study provides evidence consistent with earnings quality serving as a potential transmission mechanism in the GCG–firm value relationship, a pathway with limited evidence in developing countries. The 2019–2023 period provides unique insight into GCG resilience under pandemic disruption and recovery. Future research should expand cross-sector samples and employ multidimensional earnings quality proxies.